Peningkatan Literasi Keuangan melalui Pengenalan Investasi bagi Ibu Rumah Tangga di Merjosari Malang - Fachriyah, Nurul; Anggraeni, Octadila Laily; Septiyana, Renny Fidya; Alisha, Priscilla Keira; Maulidah, Zahrotun; Maulida, Ulrica Cinta Nur; Mulya, Daffa Haidar (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: The article aims to explore how housewives can engage in investing to build their family's financial health, secure their future, and achieve long-term financial goals like education and retirement. Methodology: Community service activities are carried out through socialisation activities to PKK RW 02 Merjosari Malang about the concept of investment for housewives, starting with providing knowledge material about various investment products and how to choose safe investment products for housewives. Results: The article suggests that investing is accessible for housewives, even with household responsibilities. With the right selection of investment products, housewives can secure their family's financial future and participate in growing their wealth. Conclusions: Investing is not as complicated as it may seem, and with careful planning, housewives can easily contribute to their family's financial well-being through strategic investment choices. Limitations: The limitations of community service are limited time and resources so that the financial literacy process can only be done through socialisation. Contribution: This community service activity introduces and fosters investment awareness for housewives.